A High‐Voltage Lithium‐Metal Batteries Electrolyte Based on Fully‐Methylated Pivalonitrile. Issue 4 (27th January 2022) - Li, Shaopeng; Fang, Shan; Li, Zhiwei; Chen, Weiyi; Dou, Hui; Zhang, Xiaogang
Abstract: Nitrile‐based electrolytes with high‐voltage have emerged as attractive candidates for high energy intensive lithium‐metal batteries (LMBs). But they are still hampered by the inherent instability of reductive lithium anodes. Herein, we propose a fully methylated pivalonitrile (PN) as a stable electrolyte solvent for LMBs. This nitrile‐based electrolyte achieves a wide electrochemical window and desired compatibility towards LMB, the assembled Li||Li symmetric cells can achieve satisfying electrochemical performance with low overpotential and high durability (500 h). The uniform and dense Li deposition investigated by operando monitoring during the Li metal plating process reveals the high Coulombic efficiency (CE) and long‐term durability. Furthermore, the full cell coupled with LiNi0.6 Mn0.2 Co0.2 O2 using this optimized electrolyte displays enhanced capacity retention (75.3 % after 300 cycles at 1 C) together with better stability and less CO2 gas production. This study provides new insights in the development of high safety electrolytes and promotes the practical application of high‐voltage lithium‐metal batteries. Abstract : For high‐voltage lithium‐metal battery : A fully methylated pivalonitrile (PN) as an electrolyte solvent for high‐voltage LMBs is proposed. TMP electrolyte based on PN and fluoroethylene carbonate (FEC) is stably compatible with lithium anode and LiNi0.6 Co0.2 Mn0.2 O2 (NCM622). The modified hybrid electrolyte reveals low viscosity, high ionic conductivity and lithium transfer numbers. A stable SEI layer could be formed in such TFP electrolyte. which inhibits the growth of lithium dendrites. At the same time, gas production and capacity attenuation under high‐voltage are inhibited.